Self‐Driven Narrow‐Band Photodetector based on FAPbBr2.5I0.5 Single Crystal for Yellow Light Intensity Meter Application - Liang, Feng‐Xia; Zhou, Liang‐Liang; Hu, Yi; Li, Shi‐Fu; Zhang, Zhen‐Yu; Li, Jing‐Yue; Fu, Can; Wu, Chun‐Yan; Wang, Li; Huang, Jian‐An; Luo, Lin‐Bao (Advanced functional materials, 2023)
Accurate and quantifiable detection of the specific wavelength is vital in different application scenarios. Herein, a novel self‐driven narrowband photodetector (NB‐PD) based on CH(NH2)2PbBr2.5I0.5 crystal film is employed for building a yellow light intensity meter. By taking advantage of the carrier collection narrowing mechanism, a sensitive NB‐PD with peak response at 580 nm and the full‐width at half‐maximum of 23 nm are successfully achieved. The asymmetric contact electrodes of Ag/Pt allow the device to work without bias. The optoelectronic analysis demonstrates that the NB‐PD achieves a maximum responsivity of 59.89 mA W−1, a fast response speed of 202/331 µs, and a high on/off ratio of 636 at zero bias. Then, through introducing the back‐end circuit, a yellow light intensity meter is constructed with the NB‐PD. The absolute error and relative error of the light meter are estimated to be lower than 0.08 mW cm−2 and 4.22%, respectively, indicating the good capability for the yellow light monitoring. Given the simple device geometry and good performance, the achieved yellow light intensity meter can also be extended to other narrowband light detection system. This work presents a filter‐free CH(NH2)2PbBr2.5I0.5 single crystal narrow‐band photodetector through a simple solution method, which exhibits good performance in the yellow light band. A yellow light intensity meter is further built by combining with the back‐end circuit, capable of detecting a wide range of yellow light intensity in real‐time.